Study protocol for writing to heal: A culturally based brief expressive writing intervention for Chinese immigrant breast cancer survivors. - Qian Lu; Di Lun; Lenna Dawkins-Moultin; Yisheng Li; Minxing Chen; Sharon Hermes Giordano; James W Pennebaker; Lucy Young; Carol Wang (PLoS ONE)
Background This study uses a randomized controlled trial (RCT) to test the health benefits of expressive writing that is culturally adapted for Chinese immigrant breast cancer survivors (BCSs) and to characterize how acculturation moderates the effects of expressive writing interventions. Methods We will recruit Chinese immigrant BCSs (N = 240) diagnosed with stage 0-III breast cancer and within 5 years of completion of primary treatment. Recruitment will occur primarily through community-based organizations and cancer registries. Participants will be randomly assigned either to a control condition to write about neutral topics or to one of two intervention conditions, self-regulation or self-cultivation, both of which aim to promote adaptive cognitive processes but differ in how they achieve this goal. The self-regulation intervention culturally adapts a Western expressive writing paradigm and incorporates emotional disclosure, whereas the self-cultivation intervention originates from Asian cultural values without disclosing emotions. Participants in all three conditions will be asked to write in their preferred language for three 30-minute sessions. The primary outcome will be quality of life (QOL) at the 6- and 12-month follow-ups, and the secondary outcomes will be perceived stress, stress biomarkers, and medical appointments for cancer-related morbidities. Discussion This project will be the first large RCT to test culturally based brief interventions to improve QOL and reduce stress among Chinese immigrant BCSs. This project is expected to address two important needs of Chinese immigrant BCSs: their unmet psychological needs and the lack of culturally competent mental health care for Chinese immigrant BCSs. The immediate product of this line of research will be empirically evaluated, culturally responsive interventions ready for dissemination to Chinese immigrant BCSs across the United States. Clinicaltrials.gov identifier NCT04754412.